2019
DOI: 10.1371/journal.pone.0210319
|View full text |Cite
|
Sign up to set email alerts
|

Quality of family planning services in Mexico: The perspective of demand

Abstract: IntroductionFamily planning (FP) is one of the key services provided by health care systems. Extending beyond matters of sexual and reproductive health, its area of influence impacts directly on the development of individuals and nations. After 60 years of intense FP activities in Mexico, and in light of recent restructuring of health service supply and financing, services need to be assessed from a user perspective.ObjectiveBased on a comprehensive conceptual framework, this article assesses the quality of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
10
0
2
Order By: Relevance
“…Sixth, we have explored some objective indicators of quality of care focused on the care process, but have not provided evidence on subjective indicators of quality; however, prior studies have shown that large populations receiving reproductive health services in Mexico perceive that interactions with health personnel are inadequate. 48 , 49 Regardless of the achievements depicted by our results, the ability to improve health care is also dependent upon the performance of health personnel. Finally, our data on postnatal care are limited.…”
Section: Discussionmentioning
confidence: 67%
“…Sixth, we have explored some objective indicators of quality of care focused on the care process, but have not provided evidence on subjective indicators of quality; however, prior studies have shown that large populations receiving reproductive health services in Mexico perceive that interactions with health personnel are inadequate. 48 , 49 Regardless of the achievements depicted by our results, the ability to improve health care is also dependent upon the performance of health personnel. Finally, our data on postnatal care are limited.…”
Section: Discussionmentioning
confidence: 67%
“…This response may have been due to me being an outsider; nevertheless, such contradictions suggest a normalization of program pressures and an internalization of the program discourse (cf. Torres-Pereda, Heredia-Pi, Ibáñez-Cuevas, & Ávila-Burgos, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Dansereau et al (2017), in focus groups in some of Chiapas’ poorest municipalities, including five Indigenous communities, found that participants described similar outstocks of hormonal methods and held misconceptions about their side effects, with some citing health care workers as their source of information. Torres-Pereda et al (2019), in interviews with mestizo participants in six Mexican states, found evidence of an “inverse availability,” a shortage of preferred methods coupled with the availability of the least preferred methods. Participants reported that pressure to choose the IUD was particularly intense during post obstetric events and especially in urban clinics, sometimes resulting in its forceful insertion.…”
Section: Discussionmentioning
confidence: 99%
“…This is because it is not uncommon for reverse availability to occur in the quality of health services, which means that the available contraceptive methods are generally not preferred by users, this is due to a lack of supply and causes unmet need. The government must also be wise in ensuring that family planning activities cover every nook and cranny (Bellows et al, 2017;Chukwuji et al, 2018;Torres et al, 2019).…”
Section: This Systematic Review Resulted In 12 Journalsmentioning
confidence: 99%
“…The availability of contraception must be adjusted to the demands and needs of the community in order to increase the use of contraception so as to reduce the incidence of unmet need. In addition, outreach efforts must be targeted according to contraceptive requests from the public, especially those hampered by poverty levels (Bellows et al, 2017;Torres et al, 2019;Tappis et al, 2015).…”
Section: Discussionmentioning
confidence: 99%